Distinct impacts of feeding frequency and warming on life history traits affect population fitness in vertebrate ectotherms - Simon Bazin; Claire Hemmer‐Brepson; Maxime Logez; Arnaud Sentis; Martin Daufresne (Ecology and Evolution, 2023)
Abstract Body size shifts in ectotherms are mostly attributed to the Temperature Size Rule (TSR) stating that warming speeds up initial growth rate but leads to smaller size when food does not limit growth. Investigating the links between temperature, growth, and life history traits is key to understand the adaptive value of TSR, which might be context dependent. In particular, global warming can affect food quantity or quality which is another major driver of growth, fecundity, and survival. However, we have limited information on how temperature and food jointly influence life history traits in vertebrate predators and how changes in different life history traits combine to influence fitness and population demography. We investigate (1) whether TSR is maintained under different food conditions, (2) if food exacerbates or dampens the effects of temperature on growth and life history traits and (3) if food influences the adaptive value of TSR. We combine experiments on the medaka with Integral Projection Models to scale from life history traits to fitness consequences. Our results confirm that warming triggers a higher initial growth rate and a lower adult size, reduces generation time and increases mean fitness. A lower level of food exacerbates the effects of warming on growth trajectories. Although lower feeding frequency increased survival and decreased fecundity, it did not influence the effects of warming on fish development rates, fecundity, and survival. In contrast, feeding frequency influenced the adaptive value of TSR, as, under intermittent feeding, generation time decreased faster with warming and the increase in growth rate with warming was weaker compared to continuously fed fish. These results are of importance in the context of global warming as resources are expected to change with increasing temperatures but, surprisingly, our results suggest that feeding frequency have a lower impact on fitness at high temperature.